Moral Value Internalization Through Satria Sejati Silat Extracurricular: Internalisasi Nilai Akhlaqul Karimah Melalui Ekstrakurikuler Silat Satria Sejati - sandra hidayat; Suhirman Suhirman; Ali Akbar jono (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Moral education plays a crucial role in shaping individual character, particularly among youth within Islamic educational environments. Specific Background: Rumah Tahfidz Bakti Ilaahi Bengkulu integrates moral education through extracurricular Satria Sejati silat as part of character formation efforts. Knowledge Gap: However, limited studies examine structured processes and contextual factors of akhlaqul karimah internalization within silat-based extracurricular activities in tahfidz institutions. Aims: This study aims to analyze the internalization process of moral values and identify supporting and inhibiting factors in Satria Sejati silat activities. Results: The findings reveal six core moral values, including morals toward Allah, the Prophet, parents, self, society, and the environment. The internalization occurs through three stages: introduction and understanding, acceptance, and internalization, implemented via habituation, role modeling, and conditioning. Supporting factors include a supportive environment, integrated teaching methods, and adequate facilities, while limited extracurricular time and diverse student backgrounds act as constraints. Novelty: This study highlights a structured integration of Islamic moral values within silat extracurricular practices in a tahfidz setting. Implications: The findings suggest that silat extracurricular activities can function as a systematic medium for moral education, contributing to character formation through integrated religious and physical training approaches. Highlights• Six moral domains identified within silat-based character education• Three-stage internalization model applied in tahfidz environment• Supporting and constraining factors mapped in extracurricular implementation KeywordsMoral Value Internalization; Islamic Moral Education; Satria Sejati Silat; Extracurricular Learning; Character Formation